Microglia inhibit photoreceptor cell death and regulate immune cell infiltration in response to retinal detachment - Okunuki, Yoko; Mukai, Ryo; Pearsall, Elizabeth A; Klokman, Garrett; Husain, Deeba; Park, Dong-Ho; Korobkina, Ekaterina; Weiner, Howard L; Butovsky, Oleg; Ksander, Bruce R; Miller, Joan W; Connor, Kip M (Proceedings of the National Academy of Sciences - PNAS, 2018)
Retinal detachment (RD) is a sight-threatening complication common in many highly prevalent retinal disorders. RD rapidly leads to photoreceptor cell death beginning within 12 h following detachment. In patients with sustained RD, progressive visual decline due to photoreceptor cell death is common, leading to significant and permanent loss of vision. Microglia are the resident immune cells of the central nervous system, including the retina, and function in the homeostatic maintenance of the neuro-retinal microenvironment. It is known that microglia become activated and change their morphology in retinal diseases. However, the function of activated microglia in RD is incompletely understood, in part because of the lack of microglia-specific markers. Here, using the newly identified microglia marker P2ry12 and microglial depletion strategies, we demonstrate that retinal microglia are rapidly activated in response to RD and migrate into the injured area within 24 h post-RD, where they closely associate with infiltrating macrophages, a population distinct from microglia. Once in the injured photoreceptor layer, activated microglia can be observed to contain autofluorescence within their cell bodies, suggesting they function to phagocytose injured or dying photoreceptors. Depletion of retinal microglia results in increased disease severity and inhibition of macrophage infiltration, suggesting that microglia are involved in regulating neuroinflammation in the retina. Our work identifies that microglia mediate photoreceptor survival in RD and suggests that this effect may be due to microglial regulation of immune cells and photoreceptor phagocytosis.